The cost associated with administering risperidone long-acting injections in the Australian community - Hertel Judy; Schrover Rudolf; Lambert Tim; Dalton Andrew; Smith Dell (BMC, 2011)
Abstract Background Risperidone long-acting injection (LAI) is mostly administered twice weekly to people with schizophrenia by nurses at community mental health centres (CMHC) or through mobile outreach visits. This study estimates the cost of resource utilisation associated with the administration of risperidone LAI and the potential savings from substituting two-weekly injections with a longer interval product of therapeutic equivalence. Methods A survey of mental health staff overseeing the administration of risperidone LAI at 253 distinct Australian CMHCs was undertaken in November 2009. For the two-week period prior to the survey, respondents were asked questions on injection time (and related tasks) and, for mobile outreach visits, distance and time travelled as well as reduction in visits. Results were stratified by Australian Standard Geographical Classification (ASGC) region. Resource use was quantified and valued in Australian dollars. Results Results are derived from 74 CMHCs, representing approximately 26% of the national average risperidone LAI unit two-week sales. Stratified average injection time (including related tasks) for risperidone LAI ranged from 18-29 minutes, with a national average of 20.12 minutes. For mobile outreach visits, average distance per patient ranged from 19.4 to 55.5 km for One Staff Visits and 15.2 to 218.1 km for More Than One Staff Visits, and average time travelled ranged from 34.1 to 54.5 minutes for One Staff Visits and 29.2 to 136.3 minutes for More Than One Staff visits. The upper range consistently reflected greater resource utilisation in rural areas compared to urban areas. If administration of risperidone LAI had not been required, 20% fewer mobile outreach visits would have occurred. Conclusions The national average saving per two-weekly risperidone long-acting injection avoided is $75.14. In 2009 in Australia, this would have saved ~$11 million for injection administration costs alone if all patients taking two-weekly risperidone LAI had instead been treated with a therapeutically equivalent long-acting injectable antipsychotic requiring one less injection per month.